IMPLEMENTASI DISTRIBUSI REQUIREMENT PLANNING DAN SAVING MATRIX UNTUK MEMINIMASI TOTAL BIAYA DISTRIBUSI DI INDUSTRI BAHAN KIMIA - Ong, Johan Oscar; Saraka, Arianto (Jurnal Ilmiah Teknik Industri, 2013)
Planning and scheduling of the distribution of goods in PT. Senatama Laboranusa are not well coordinated, so the demand for each product is out of control, which results in deficiency or excess of inventories in both of the factories and each warehouse. This problem will affect the distribution cost incurred by the company. In this study, the distribution data process is done by using Distribution Requirement Planning method and route distribution processing by using Saving Matrix, in which both of these methods can group the delivery schedule and flow of distribution route regularly. PO Release, which contains time, order amount of each area, and lot size EOQ (Economic Order Quantity) method used; will be generated from the calculation of DRP. From the calculation of Saving Matrix, route order sequence is applied by using Nearest Neighbor method. After the implementation of Distribution Requirement Planning, the cost reduction resulted is 29.75% and the difference in distance after the application of Saving Matrix is 983.3 Km. With a good distribution activity planning and scheduling, the success rate in meeting the customer demand would be more optimal, while sales performance increases in fulfilling orders in a timely manner andÂ  appropriate amount, hence the distribution costs can be kept as minimum as possible.